2022
DOI: 10.1002/ps.7202
|View full text |Cite
|
Sign up to set email alerts
|

Controlled‐release alginate‐bentonite polymer gel granules of emamectin benzoate and control efficacy against Spodoptera frugiperda

Abstract: Background: The fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith), is known to cause large agricultural production losses. Emamectin benzoate is one of the most effective insecticides to control this pest; however, its effective time is not sufficiently long to control FAW. Therefore, it is important that new controlled insecticide formulations with new application methods are developed.Results: A series of emamectin benzoate polymer gel granules were prepared with sizes ranging from 0.95 to 1.5 mm. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The experimental values were basically consistent with the model optimization simulation values, which indicates that the optimization model had good reliability. Response surface method optimization determined the quality of each factor affecting the granule encapsulation efficiency, and the granule formulation optimized by the response surface method was significantly improved compared to the conventional artificial formulation. , Typical photographs of Eb·He-loaded composite beads are shown in Figure . The beads obtained were generally spherical in shape and the size varied in the range from 1.1 to 1.5 mm for the composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental values were basically consistent with the model optimization simulation values, which indicates that the optimization model had good reliability. Response surface method optimization determined the quality of each factor affecting the granule encapsulation efficiency, and the granule formulation optimized by the response surface method was significantly improved compared to the conventional artificial formulation. , Typical photographs of Eb·He-loaded composite beads are shown in Figure . The beads obtained were generally spherical in shape and the size varied in the range from 1.1 to 1.5 mm for the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research has also shown that the effective time of granules for pest control is longer than reported spraying pesticide solutions, and the control efficacy can be significantly improved. 21 In this paper, a series of particles were prepared by using alginate and carboxymethyl chitosan as the substrate and the combination of Eb and He as the model pesticide. The encapsulation rate as an evaluation index via nonlinear mathematical model fitting and the preparation process was optimized.…”
Section: Introductionmentioning
confidence: 99%
“…The Korsmeyer–Peppas and Higuchi’s model have often been used to describe the law and control mechanism of drug release in polymers. ,, In order to understand the release properties of acitretin salt particles, the Korsmeyer–Peppas model (eq ) and Higuchi’s model (eq ) were used to fit the release data of EB. M t / M 0 = k t n M t / M 0 = k t 1 / 2 where M t / M 0 is the drug release rate at time t , k is a constant, and n is the diffusion index. The fitting results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The Korsmeyer–Peppas and Higuchi’s model have often been used to describe the law and control mechanism of drug release in polymers. 10 , 33 , 34 In order to understand the release properties of acitretin salt particles, the Korsmeyer–Peppas model ( eq 1 ) and Higuchi’s model ( eq 2 ) were used to fit the release data of EB. where M t / M 0 is the drug release rate at time t , k is a constant, and n is the diffusion index.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation